Lack of Interest of Junior High School/MTs Graduates in Vocational Education (SMK) in Indonesia: Analysis of Factors and Strategic Recommendations - Sunarsih, Eti; Handoyo, Eko; Rokhman, Fathur (Universitas Negeri Semarang, 2025)
Vocational education (SMK) has a strategic role in preparing human resources ready for work. Indonesia has targeted an increase in the proportion of vocational school students in order to prepare a productive workforce and reduce the unemployment rate of secondary education graduates (Ministry of Education and Culture, 2020). However, in reality, the number of students who graduated from junior high school/MTs who choose to continue to vocational schools is still lower than those who continue to high school or MA (BPS, 2023). The results of a mini research conducted by the researcher on grade IX students of SMP 1 Dawe Kudus for the 2024/2025 Academic Year through a questionnaire in the form of a google form about the selection of further study to SMA/SMK/MA/Pondok Pesantren, also show that high school is still more in demand by students. Of the 206 students, 143 students chose high school, 54 students chose vocational school, 3 students chose MA, and 6 students did not continue their studies. This article examines the factors that cause low interest in vocational schools and provides strategic recommendations to increase vocational education participation. Through literature studies and data analysis, it was found that negative public perception of vocational schools, inequality of quality between vocational schools, and weak linkages with the world of work are the main obstacles. It is necessary to transform the image of vocational schools, revitalize the curriculum, and increase synergy with industry to attract more students to vocational education.